The Role Of Education On The Management Of Healthy Lifestyle Control To Avoid Non-Infectious Disease And Severe Disease Complication In The Village Of Buluh Cina Hamparan Perak - Rusdiana Rusdiana (Talenta Publisher Universitas Sumatera Utara, 2025)
Hypertension and DM are non-infectious diseases that require proper and careful lifestyle management. These diseases not only cause complications of heart attack, heart failure and stroke, but in many cases often lead to other severe complications. It is necessary to increase awareness and determination to carry out proper management in management independently to avoid severe disease complications. A good understanding of prevention and self-management such as blood sugar and blood pressure control and the use of drugs in accordance with the doctor's recommendations are needed. To improve understanding of these diseases for prevention for those who have not suffered and self-management for those who have suffered, education is needed with the scope of things that need to be done for diabetics and also hypertension which many of our society still do not understand. This community service programme aims to provide education on the understanding of hypertension and type 2 DM in terms of management such as diet, daily activities and exercise, regular medication and avoiding stress. The target of this programme is the community in Buluh Cina village, Hamparan Perak sub-district. With this education, it is hoped that the local community can understand the management of a healthy lifestyle to avoid severe complications.